Hubungan Antara Kepatuhan Penggunaan Masker dengan Kapasitas Fungsi Paru pada Sukarelawan Pengatur Lalu Lintas (SUPELTAS) Surakarta - Khanastren, Suha, Sri Darnoto, SKM, M.PH (2017)
SUPELTAS worked which on the road can be exposed by air pollution and risk with respiration trouble and also influence of their health lung. DIKYASA have suggested to use mask while they work, but still a lot SUPELTAS did not use mask. This study aimed to analyze the relationship between compliance of mask use with lung function capacity in volunteer of regulator traffic of Surakarta. This type of research is observasional analytic with cross sectional approach. The study population is SUPELTAS Surakarta as much 50 people taken with exhaustive sampling technique. Data analysis using Fisher's Exact test. The results of research indicated that there is correlation between compliance of mask use with lung function capacity in volunteer of regulator traffic of Surakarta (p = 0,018).